2013
DOI: 10.1111/ejn.12109
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of bilateral communication in the suprachiasmatic nucleus

Abstract: The central circadian pacemaker of the suprachiasmatic nuclei (SCN) is a bilaterally symmetrical structure. Little is known about the physiological mechanisms underlying communication between the left and right SCN and yet the degree of synchronization between SCN neurons can have a critical impact on the properties of the circadian system. In this study, we used electrophysiological tools and calcium (Ca(2+) ) imaging to examine the mechanisms underlying bilateral signaling in mouse SCN. Electrical stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 62 publications
2
32
1
Order By: Relevance
“…This possible involvement of the glutamate receptor is especially interesting, because the glutamate receptor has also been implicated in communication between the SCN and the RHT, which occurs in the core SCN region (53). Thus, our results support the hypothesis that antiphasic oscillation between SCN halves in constant light is made possible by distinct signaling mechanisms in the SCN rather than a weaker coupling strength between halves (52,54).…”
Section: B Asupporting
confidence: 83%
See 1 more Smart Citation
“…This possible involvement of the glutamate receptor is especially interesting, because the glutamate receptor has also been implicated in communication between the SCN and the RHT, which occurs in the core SCN region (53). Thus, our results support the hypothesis that antiphasic oscillation between SCN halves in constant light is made possible by distinct signaling mechanisms in the SCN rather than a weaker coupling strength between halves (52,54).…”
Section: B Asupporting
confidence: 83%
“…The SCN is often thought to be most tightly connected within each half, given the ability of the left and right SCN to oscillate in antiphase in animals exposed to constant light (50,51). However, tight bilateral coupling is reflective of previous studies that showed significant coupling between the halves and further implicates the glutamate receptor in this communication (52). This possible involvement of the glutamate receptor is especially interesting, because the glutamate receptor has also been implicated in communication between the SCN and the RHT, which occurs in the core SCN region (53).…”
Section: B Amentioning
confidence: 99%
“…Unilateral lesion of the SCN abolished the splitting and established a single rhythm of behavioral activity (Pickard and Turek 1982). In normal conditions, the left and right SCN are strongly connected with each other even in isolated culture (Michel et al 2013), and the functional connection is important for coupling of their free-running rhythms, as observed in wild-type SCN slices over 10 d (Fig. 2).…”
Section: Discussionmentioning
confidence: 75%
“…Ca 2+ measurements were performed as described previously (35). Brain slices that included the SCN were loaded with the ratiometric Ca 2+ indicator dye fura-2-acetoxymethyl ester (Fura-2-AM).…”
Section: Methodsmentioning
confidence: 99%